2019
DOI: 10.1007/s00044-019-02472-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification of ellipticine derivatives with alkyl groups of varying length is influential on their effects on human DNA topoisomerase II: a combined experimental and computational study

Abstract: The compounds reducing tumor cell viability and disrupting DNA topoisomerase reactions have been widely used in anticancer drug development. Ellipticine (5,carbazole) is a potent intercalating agent that interferes with nucleic acid processing through interaction with DNA topoisomerase II. Although ellipticine is a wellcharacterized compound, it is not a widely-accepted drug due to the adverse effects detected upon administration. We have previously reported two novel ellipticine derivatives, N-methyl-5-demeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Compounds 3, 5, 7, 19, 31, 35 and 37 all inhibited human topoisomerase II activity. [36,53,70,74,76] The elipticine derivative 38, a Topo II-targeting compound, induces the formation of DNA breaks and the suppression of ALTassociated phenotypes in telomerase-negative cells. [77] The mechanism of Topo II inhibition is shown in Figure 5.…”
Section: The Interaction Between Ellipticine Derivatives Dna and Topo IImentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 3, 5, 7, 19, 31, 35 and 37 all inhibited human topoisomerase II activity. [36,53,70,74,76] The elipticine derivative 38, a Topo II-targeting compound, induces the formation of DNA breaks and the suppression of ALTassociated phenotypes in telomerase-negative cells. [77] The mechanism of Topo II inhibition is shown in Figure 5.…”
Section: The Interaction Between Ellipticine Derivatives Dna and Topo IImentioning
confidence: 99%
“…described the synthesis, characterization, and activity of five new salts of N‐methyl 5‐demethyl ellipticine with several organic halides and their effects on human topoisomerase II enzymes and reported that lead compound 37 exhibited potent antitumor activity against HeLa, SiHa, MCF‐7 and MDA‐MB‐231 cell lines, with IC 50 values of 0.09, 0.46, 0.42 and 0.34 μM, respectively. Their mechanistic investigation revealed that compound 37 had a considerable inhibitory effect on the catalytic activity of human topoisomerase II [76] …”
Section: Antitumor Activity and Mechanism Of Action Of Ellipticine De...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ellipticine derivatives such as 9-hydroxy-2-methylellipticinium acetate (NHME) had been introduced into the market, but were later withdrawn. [6] The search for other ellipticine derivatives is under way [10][11][12][13][14][15][16]. However, low water solubility of ellipticine derivatives is a crucial obstacle for the wide practical application in cancer therapies.…”
Section: Introductionmentioning
confidence: 99%